2000
DOI: 10.1177/1541931200044028115
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Familiarity and Risk Perception on Workplace Warning Compliance

Abstract: Consumer products cause millions of injuries every year at a total cost of billions of dollars in medical costs, lost wages and reductions in quality of life. To prevent injuries, manufacturers often place warnings on dangerous products and materials with information about proper handling and possible injuries. In order for a warning to be effective, it must be seen, read, comprehended, and followed. A breakdown iu any of these stages will hinder the warning from preventing an injury. This study is a naturalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…RP studies have analyzed popular knowledge, attitudes and behaviors related to water reuse [35], pesticides [36], loss of agro-biodiversity [37] and West Nile virus [38]. When the object of the RP study is a product, RP refers to how much that people feel that their safety is threatened by using it [39]. To our knowledge there are no published studies relating cleaning products, RP and EA in the developing world in general and Mexico in particular, and cleaning products contamination studies are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…RP studies have analyzed popular knowledge, attitudes and behaviors related to water reuse [35], pesticides [36], loss of agro-biodiversity [37] and West Nile virus [38]. When the object of the RP study is a product, RP refers to how much that people feel that their safety is threatened by using it [39]. To our knowledge there are no published studies relating cleaning products, RP and EA in the developing world in general and Mexico in particular, and cleaning products contamination studies are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…We propose that familiarity with common warning stimuli accounts for this result; for example, a triangular frame is often used on traffic signs to represent a warning or a hazardous situation, whereas an octagonal frame is not used to communicate danger in this context. Such familiarity with warning stimuli may be achieved through participants' direct experience as well as through observations of use, exposure to warnings, or experience with similar products (Ortiz et al, 2000;Riley, 2014). Consequently, in the present experiment, the heightened perception of hazardousness was greater for the familiar triangle than that for the less familiar octagon.…”
Section: Frames Surrounding the Warning Symbolmentioning
confidence: 77%
“…In particular, the more familiar the terms are, the lower the perceived risk. The more familiar the terms used for products, the lower the risk perceived by consumers [26,27]. Fischer and Frewer [53] conducted a study on risk perception for foods and found that the higher the familiarity with food hazards, the lower the measure of hazard perception.…”
Section: Familiaritymentioning
confidence: 99%